Analysis of the structure and abnormal photoluminescence of a red-emitting LiMgBO3:Mn2+ phosphor. Issue 37 (31st August 2018) - Wu, Liwei; Bai, Yuxing; Wu, Li; Yi, Huan; Zhang, Xinzheng; Zhang, Lixin; Kong, Yongfa; Zhang, Yi; Xu, Jingjun
Abstract : In LiMgBO3 :Mn 2+ phosphor, the origin of the abnormal luminescence (deep red emission) of Mn 2+ in five-coordinated configuration has been disclosed. Abstract : Mn 2+ is attracting increasing attention due to its potential application as an activated ion in the phosphors. In this study, a rare-earth free phosphor, LiMgBO3 :Mn 2+, was synthesized using a high temperature solid-state reaction. Combined with X-ray diffraction and PL/PLE as well as first-principles calculation, the coordination environment of Mn 2+ was disclosed, revealing that Mn 2+ ions were inclined to occupy two partially filled Li sites. Under 427 nm-excitation, an abnormal deep red emission band centered at 705 nm was observed. This was due to the strong crystal field environment of Mn 2+ induced by the extremely distorted five-coordinated sites, which was proved by the electronic band structure obtained from the density functional theory calculations. In addition, the luminescence intensity and thermal stability of LiMgBO3 :Mn 2+ was significantly enhanced when Li + was replaced by Na + and K + . This study disclosed the origin of the abnormal luminescence of Mn 2+ in LiMgBO3 and further enriched our understanding of the abnormal luminescence of Mn 2+ in special crystal structures (five-coordinated configuration).